2018
DOI: 10.3390/robotics7030033
|View full text |Cite
|
Sign up to set email alerts
|

Validating Autofocus Algorithms with Automated Tests

Abstract: Abstract:For an automated camera focus, a fast and reliable algorithm is key to its success. It should work in a precisely defined way for as many cases as possible. However, there are many parameters which have to be fine-tuned for it to work exactly as intended. Most literature only focuses on the algorithm itself and tests it with simulations or renderings, but not in real settings. Trying to gather this data by manually placing objects in front of the camera is not feasible, as no human can perform one mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Hence, the computer needs a reliable autofocus algorithm to quantify the level of image sharpness. Some reports have demonstrated the implementation of many image quality metrics for actual applications [2]- [9]. As technologies keep evolving, numerous discussions and new methods have been proposed related to this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the computer needs a reliable autofocus algorithm to quantify the level of image sharpness. Some reports have demonstrated the implementation of many image quality metrics for actual applications [2]- [9]. As technologies keep evolving, numerous discussions and new methods have been proposed related to this topic.…”
Section: Introductionmentioning
confidence: 99%
“…By hill-climbing searching, determining the peak value can help to determine the required focus based on a simple configuration, which is easy to handle and stable but rather time-consuming and has a very limited effective depth of focus. We have found that many research articles [31][32][33][34][35][36][37] have investigated the improvement of the algorithm using software and tried to make the application of the technique to the product line possible.…”
Section: Introductionmentioning
confidence: 99%